2014
DOI: 10.1016/j.pjnns.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in carriers of glucocerebrosidase gene mutation in Parkinson disease patients

Abstract: The N370S GBA mutation is the risk factor for cognitive impairment in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 9 publications
1
17
0
4
Order By: Relevance
“…In cross-sectional analyses of GBA mutations in PD patients, earlier disease onset, increased cognitive impairment, a greater family history of PD, and more frequent pain were reported in patients with mutations, compared with no mutations (Chahine et al, 2013;Clark et al, 2007;Gan-Or et al, 2008;Kresojevic et al, 2015;Lwin et al, 2004;Malec-Litwinowicz et al, 2014;Mitsui et al, 2009;Neumann et al, 2009;Nichols et al, 2009;Seto-Salvia et al, 2012;Sidransky et al, 2009;Swan and SaundersPullman, 2013;Wang et al, 2012). Recently, a few prospective studies have investigated clinical features of PD with GBA and showed a more rapid progression of motor impairment and cognitive decline in GBA mutation cases than in PD controls (Beavan et al, 2015;Brockmann et al, 2015;Winder-Rhodes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In cross-sectional analyses of GBA mutations in PD patients, earlier disease onset, increased cognitive impairment, a greater family history of PD, and more frequent pain were reported in patients with mutations, compared with no mutations (Chahine et al, 2013;Clark et al, 2007;Gan-Or et al, 2008;Kresojevic et al, 2015;Lwin et al, 2004;Malec-Litwinowicz et al, 2014;Mitsui et al, 2009;Neumann et al, 2009;Nichols et al, 2009;Seto-Salvia et al, 2012;Sidransky et al, 2009;Swan and SaundersPullman, 2013;Wang et al, 2012). Recently, a few prospective studies have investigated clinical features of PD with GBA and showed a more rapid progression of motor impairment and cognitive decline in GBA mutation cases than in PD controls (Beavan et al, 2015;Brockmann et al, 2015;Winder-Rhodes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…PD etiology is largely unknown, although some authors have suggested the nasal entry of viruses, such as herpes simplex virus type 1 (HSV1), as a possible cause of the disease [34]. Genetic factors, such as glucocerebrosidase gene mutation, are also involved with a variable prevalence of up to 19 % [35]. Other possible causes of the disease could be epithelial or bulbar damage initiated by exposure to airborne environmental toxins or focal head trauma [12].…”
Section: Introductionmentioning
confidence: 99%
“…Neurodegeneration is the umbrella term covering the progressive loss of neuronal structure or function, resulting in irreversible brain damage. The incidence of NDDs, including Alzheimer's disease (AD), multiple sclerosis (MS), Parkinson's disease (PD), Huntington's disease (HD) and amyotrophic lateral sclerosis (ALS), is increasing at an alarming rate worldwide [1,8,9]. However, the etiologies of NDDs are not well understood.…”
Section: Introductionmentioning
confidence: 99%